2019
DOI: 10.1155/2019/8765954
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 Modulators in Experimentally Induced Liver Injury

Abstract: This article is directed at highlighting the involvement of the endogenous stress sensor SIRT1 (silent information regulator T1) as a possible factor involved in hepatoprotection. The selective SIRT1 modulators whether activators (STACs) or inhibitors are being tried experimentally and clinically. We discuss the modulation of SIRT1 on cytoprotection or even cytotoxicity in the liver chemically injured by hepatotoxic agents in rats, to shed light on the crosstalk between SIRT1 and its modulators. A combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 130 publications
(143 reference statements)
0
42
0
Order By: Relevance
“…SIRT1 is an NAD+-dependent protein lysine deacetylase of the sirtuin family and exerts many physiological effects, mediating inflammation, cell survival, tissue regeneration, and stress responses [31]. SIRT also plays roles in modulating histone and nonhistone substrates, including DNA repair proteins and transcription factors (e.g., p53, nuclear factor-κB, and PGC-1α) [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SIRT1 is an NAD+-dependent protein lysine deacetylase of the sirtuin family and exerts many physiological effects, mediating inflammation, cell survival, tissue regeneration, and stress responses [31]. SIRT also plays roles in modulating histone and nonhistone substrates, including DNA repair proteins and transcription factors (e.g., p53, nuclear factor-κB, and PGC-1α) [32].…”
Section: Discussionmentioning
confidence: 99%
“…xanthine oxidase and thiobarbituric acid, respectively. All assays were performed with kits (Nanjing Jiancheng Bioengineering Research Institute, Nanjing) [31]. A lipid peroxidase MDA detection kit (Jiancheng Biotechnology, Nanjing, Jiangsu, China) was used to determine the MDA content, and a micro flat-panel reader was used to determine the absorbance at 530 nm.…”
Section: Assessment Of Malondialdehyde (Mda) Levels and Superoxide DImentioning
confidence: 99%
“…[ 15 ] With oxidative stress, SIRT1 greatly protects the cell through the deacetylation of substrate proteins, which results in cell survival. [ 16 ] SIRT1 has the ability to deacetylate key metabolic players including peroxisome proliferator‐activated receptor (PPAR) gamma coactivator 1 alpha (PGC1α), a strategic controller of oxidative metabolism, and it induces enzymatic antioxidants. [ 17‐19 ] The forkhead box O (FOXO) transcription factor is involved in diverse cellular and physiological processes including cell proliferation, apoptosis, ROS response, longevity, cancer, and regulation of cell cycle and metabolism, [ 20 ] and it is one of the targets of SIRT.…”
Section: Introductionmentioning
confidence: 99%
“…Palmitate (PA) is a saturated fatty acid that induces IR in various scenarios, including hepatocytes [11]. Studies have shown that deacetylase sirtuin-1 (SIRT1) plays an important role in the regulation of liver metabolism [12][13][14]. SIRT1 agonists can cause the translocation of nuclear transcription factor FOXO1 in liver cells, inhibit gluconeogenesis, and improve insulin sensitivity [15].…”
Section: Introductionmentioning
confidence: 99%